Entrepreneurship Education in Tertiary Institutions as Tool for Reducing Unemployment - OLASENI , Vivian Morenike, (Journal of Ecohumanism, 2025)
This study explored the role of entrepreneurship education in alleviating unemployment. The research was guided by four key questions, and relevant literature was reviewed to provide context. A descriptive survey research design was employed, focusing on the undergraduate student population at Adekunle Ajasin University, Akungba-Akoko. The sample consisted of 300 randomly selected students from six faculties within the university, chosen using a simple random sampling technique. Data were collected via a self-designed questionnaire and analyzed using frequency counts and simple percentages. The study’s findings revealed that skills such as design, food catering, photography, laundry/dry cleaning, barbering/hairdressing, web design, bead making, music, makeup artistry, and event planning can empower Nigerian graduates to become entrepreneurs and help reduce unemployment. Furthermore, the benefits of entrepreneurship education for Nigerian graduates were found to include self-employment, job creation in rural areas, opportunities to harness personal potential, and enhanced ability to adapt to societal changes. Challenges identified include inadequate funding from both government and non-governmental organizations, a shortage of qualified instructors, insufficient teaching materials, equipment, and infrastructure, lack of capital for starting businesses, and a poor business environment. Suggested solutions to these challenges include creating a supportive business environment, ensuring the availability of qualified teachers, establishing funding sources for entrepreneurs, and providing necessary teaching resources and infrastructure. Based on these findings, the study recommends that Nigerian graduate entrepreneurs acquire skills such as those listed above to help reduce the unemployment rate. It also calls on the government to improve the infrastructure for entrepreneurial activities, provide adequate teaching resources, increase funding for entrepreneurial programs, and create diverse funding opportunities for Nigerian graduate entrepreneurs.